Influence of Exercise on Exhausted and Senescent T Cells: A Systematic Review - Donovan, Thomasina; Bain, Amanda L.; Tu, Wenjuan; Pyne, David B.; Rao, Sudha (Frontiers in Physiology, 2021)
The impaired effector function of exhausted and senescent T cells is implicated in cancer progression and inadequate vaccine responses. Exercise has been shown to improve cancer therapy and vaccine efficacy, most likely by improving immune function. However, given inconsistent terminology and definitions, the interactions between exercise and exhausted and senescent T cells remain unclear. We therefore performed a systematic review to investigate the effect of exercise on senescent and exhausted CD8+ T cell populations clearly defined by protein surface markers. Thirty articles were included, with the majority (n=24) reporting senescent T cell populations defined according to a variety of surface markers. Repeated exercise was shown to be beneficial through limiting the accumulation of senescent and exhausted CD8+ T cells. This outcome is likely related to exercise-induced preferential mobilization of senescent T cells promoting apoptosis in the peripheral blood compartment. Future studies need to determine the clinical relevance of this effect in cancer prevention and vaccine efficacy. Data regarding exercise and exhausted T cells are limited due to a lack of available high-quality studies. Future studies require the control of confounding variables such as sex and cytomegalovirus status, and consistent definitions of exhausted and senescent T cell populations to improve comparisons between studies and interventions.